2016
DOI: 10.1371/journal.pone.0160924
|View full text |Cite
|
Sign up to set email alerts
|

Kinase Gene Expression Profiling of Metastatic Clear Cell Renal Cell Carcinoma Tissue Identifies Potential New Therapeutic Targets

Abstract: Kinases are therapeutically actionable targets. Kinase inhibitors targeting vascular endothelial growth factor receptors (VEGFR) and mammalian target of rapamycin (mTOR) improve outcomes in metastatic clear cell renal cell carcinoma (ccRCC), but are not curative. Metastatic tumor tissue has not been comprehensively studied for kinase gene expression. Paired intra-patient kinase gene expression analysis in primary tumor (T), matched normal kidney (N) and metastatic tumor tissue (M) may assist in identifying dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…integrins, heparanases, and matrix metalloproteinases) have inhibitors that are currently under study in phase I/II/III clinical trials [27][28][29][30][31][32][33]. Kinase genes have also recently been reported to be upregulated in metastatic tumors relative to primary ccRCC tumors [34]. Thus, further study is required to determine whether ECM or kinase genes represent therapeutic targets in metastatic RCC.…”
Section: Discussionmentioning
confidence: 99%
“…integrins, heparanases, and matrix metalloproteinases) have inhibitors that are currently under study in phase I/II/III clinical trials [27][28][29][30][31][32][33]. Kinase genes have also recently been reported to be upregulated in metastatic tumors relative to primary ccRCC tumors [34]. Thus, further study is required to determine whether ECM or kinase genes represent therapeutic targets in metastatic RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Ge et al reported that a rare variant of CHEK2, rs17879961, was associated with decreased risk of renal cell cancer ( 23 ). A study by Ghatalia et al ( 24 ), which compared intra-patient kinase gene expression between RCC and matched normal kidney samples, identified CHEK2 as one of the top 10 overexpressed kinases in metastatic RCC, suggesting a pathological role of activated CHEK2 in RCC. The aim of this retrospective study was to further evaluate the role of I157T and CHEK2*1100delC mutations of CHEK2 gene in ccRCC.…”
Section: Introductionmentioning
confidence: 99%
“…55 A recent study showed that it is overexpressed in metastasis compared to primary RCC tumors. 56 In addition, AURKA is involved in the pathogenesis or progression of hepatocarcinoma, 35 bladder, 36 breast, 37 liver, 38 gastric, 57 colon, 58 non-small cell lung, 59 and pancreatic 60 cancers. AURKB modulates drug response in non-small cell lung, 61 and breast cancers.…”
Section: Discussionmentioning
confidence: 99%